THE APPLICATION OF STRICT LIABILITY ON CORPORATION OF FOREST AND LAND FIRES ON THE PERSPECTIVE OF ENVIRONMENTAL LAW AND FIQH AL-BIAH (An analysis of decision Number:456/Pdt.G-LH/2016/PN Jkt. Sel) - Eko Nur Cahyo; Nizham Mahmudi Muttaqin (Ijtihad, 2019)
Problems related to environmental damage is a hottopic discussed today. Aside from being concerned with thebasic needs of all humanity, environmental degradationgoes hand in hand with economic and technologicaladvancements which are expected to lead to humanbenefit and prosperity. One of the efforts made to provideenvironmental protection is to adopt the application ofStrict Liability in Anglo Saxon countries in solving cases ofenvironmental damage caused by corporations. Accordingto the principle of strict liability, the claim is not basedon an element of error but is based on the impact of thedefendant’s actions. One example of a forest and landfire that was successfully decided based on Strict Liabilityis the decision number: 456 / Pdt.G-LH / 2016 / PNJkt Sel. On the other hand, environmental problems arealso closely related to spiritual issues. As a living solution,Islam provides views through Muslim scholars regardingenvironmental issues with the inception of the idea of Al-Biah Fiqh. The approach taken through Maqasid Syariah,by combining hifdz al-biah as a matter of dharuriyat. Thiswas supported by Mustafa Abu Sway and also Ali Yafie.The results of this study indicate a paradigm differencebetween the more reductionist environmental law and amore holistic environmental law. But even so, Strict Liabilitycan be adjusted with fiqh al-biah with several conditions